Feasibility analysis of a novel solid-state H2 storage reactor concept based on thermochemical heat storage: MgH2 and Mg(OH)2 as reference materials. (7th December 2016) - Bhouri, M.; Bürger, I.; Linder, M.
Abstract: This paper discusses the feasibility of a novel adiabatic magnesium hydride (MgH2 ) reactor concept based on thermochemical heat storage. In such a concept, the heat of reaction released during the absorption of hydrogen is stored by a thermochemical material in order to be reused in a subsequent desorption stage. Magnesium hydroxide (Mg(OH)2 ) has been selected as the suitable material for integration into the MgH2 storage system due to its thermodynamic properties. An analytical formulation of hydrogen absorption time is used to determine the range of the geometrical characteristics of the two storage media, their properties and their operating conditions. The advantage of the proposed new concept is the possibility to reduce the mass of the heat storage media by a factor of 4 compared to phase change material, improving then the gravimetric system capacity as well as its total cost. The second advantage is an improved flexibility of the operating pressure conditions for MgH2 absorption reaction and Mg(OH)2 dehydration reaction that enables shorter hydrogen absorption times by ensuring larger temperature gradients between the two storage media. Highlights: Adiabatic solid-state H2 storage system based on thermochemical storage. Analytical study to calculate the H2 absorption time of the proposed reactor. Dependence of H2 absorption time on reactor geometry. Dependence of H2 absorption time on the properties of thermochemical material. Dependence of H2 absorption time on operational conditions.